Exploring Teachers' Perspectives on the Use of Kahoot in English Language Teaching: Enhancing Engagement and Learning Outcomes - Tampubolon, Jonris; Siahaan, Desta Gloria; Bouk, Edmundus (English Lecturers and Teachers Association (ELTA), 2025)
Game-based learning such as Kahoot! has transformed the conventional classrom settings into more fun and interactive learning experiences. Kahoot! as a digital game-based student response system allows teachers and students to connect through competitive knowledge games. It encourages active learning and provides assistance to educators in the process of developing quizzes with multiple-choice questions. The purpose of this research is to investigate teachers’ perceptions of Kahoot in English Language Teaching and to assess the impact of Kahoot on student engagement and learning outcomes from the teachers' viewpoint. Mixed-method design was used to explore deeper perspectives and experiences of respondents. Survey and semi-structured interviews were employed to collect the data. The collected data were analyzed using both qualitative and quantitative methods. There were 50 primary school teachers selected through purposive sampling technique as respondents of this research. The findings of this research demonstrate that Kahoot is an effective gamified-learning tool to enhance student engagement and motivation in learning process. However its limitation in presenting deeper learning and its technical issues associated with the internet connectivity and devices capability must be carefully considered. Keywords: Kahoot, English Language Teaching, Student Engagement, Learning Outcomes